Dermatoscopy of the pruritic variant of trichostasis spinulosa: A noninvasive diagnostic method - Mithin Kumar Balasundaram; Logamoorthy Ramamoorthy (Wolters Kluwer Medknow Publications, 2023)
Trichostasis spinulosa is a hair follicular disorder hyperkeratotic dilated hair follicles with retention of multiple vellus hairs. It is a common disorder often unrecognized by patients. Dermatoscopy helps in diagnosis and deciding the treatment of this disorder avoiding unnecessary skin biopsy. Here, we report a case of a pruritic variant of trichostasis spinulosa with characteristic signs of hair retention in dermatoscopy.